2018
DOI: 10.1080/14659891.2018.1497102
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Cognitive Assessment (MoCA) as a cognitive screen in addiction health care: A validation study for clinical practice

Abstract: Objective: The current study assessed the criterion validity of the Montreal Cognitive Assessment (MoCA) as a short cognitive screen for use in addiction health care. Method: Eighty-two patients were assessed with two parallel versions of the MoCA; at intake (baseline) and directly preceding an extensive neuropsychological assessment (NPA) approximately 8 weeks later (follow-up). Results: Of all included patients, 54.9% were classified as having substance-induced neurocognitive disorder. The most common primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 35 publications
1
30
1
Order By: Relevance
“…Post‐hoc tests revealed that only patients using alcohol performed significantly worse on the MoCA total score than those using cannabis (Table ). However, taking into consideration the sensitivity and specificity of the MoCA in addiction care , a rather high proportion of patients with actual cognitive impairments may remain undetected, while at the same time cognitively intact patients are classified as being cognitively impaired by the MoCA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Post‐hoc tests revealed that only patients using alcohol performed significantly worse on the MoCA total score than those using cannabis (Table ). However, taking into consideration the sensitivity and specificity of the MoCA in addiction care , a rather high proportion of patients with actual cognitive impairments may remain undetected, while at the same time cognitively intact patients are classified as being cognitively impaired by the MoCA.…”
Section: Resultsmentioning
confidence: 99%
“…The small number of patients using sedatives and gamma‐hydroxybutyrate were not included in the comparisons making it impossible to conclude about consequences on cognitive functioning for these substances. Finally, the rather low sensitivity and specificity of the MoCA for use in addiction care may have influenced our results and therefore the actual prevalence of cognitive impairments may well be different than that currently found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MoCA was developed to be more sensitive to mild cognitive impairment in geriatric populations than other screeners, like the Mini Mental State Examination (MMSE; Folstein et al 1975), and has been translated into nearly 100 languages. Besides geriatrics, the MoCA is widely used in, for instance, substance use, HIV and hepatitis C (Bassiony et al 2015;Bruijnen et al 2016;Copersino et al 2009;Janssen et al 2015). Although the MoCA has gained wide support, research focussing on its psychometric properties, such as alternate-form-, test-retest-and inter-rater reliability, has yielded mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they suggested to add one 'correction point' to scores of individuals with 12 years of education or less. Bruijnen et al (2019) recently proposed a more fine-grained correction method based on the level of education, rather than its duration, where individuals with a low level of education receive two additional points and those with an average level of education receive one additional point. Only one study correlated MoCA scores with general intellectual abilities and found a correlation of 0.64 (Sugarman and Axelrod 2014).…”
Section: Introductionmentioning
confidence: 99%